AUY922 effectively targets against activated B cell subtype of diffuse large B-cell lymphoma and low-grade lymphoma cells harboring genetic alteration-associated nuclear factor-κB activation. Issue 9 (2nd September 2015) - Tsai, Hui-Jen; Shih, Neng-Yao; Kuo, Sung-Hsin; Cheng, Ann-Lii; Lin, Hui-You; Chen, Tsai-Yun; Chang, Kung-Chao; Lin, Sheng-Fung; Chang, Jeffrey S.; Chen, Li-Tzong
Abstract : Recurrent genetic alterations that are frequently observed in some low-grade lymphomas, such as activated B cell subtype of diffuse large B-cell lymphoma (ABC-DLBCL) and mucosa-associated lymphoid tissue type lymphoma (MALT lymphoma) are usually associated with nuclear factor-κB (NF-κB) activation and confer resistance to therapy. In this study, we investigated the therapeutic efficacy and molecular mechanisms of AUY922, a novel Hsp90 inhibitor, in representative cell lines OCI-Ly3 (ABC-DLBCL) and MA-1 (a low-grade lymphoma cell line with t(14;18)/IgH-MALT1translocation) to explore its potential use in the treatment of refractory B-cell lymphoma. Our results showed that AUY922 effectively induced growth inhibition and apoptosis of OCI-Ly3 and MA-1 cells, which were accompanied by down-regulation of the expression levels of NF-κB and Bcl-2 family proteins, as well as molecules of multiple signaling pathways involving cell proliferation, growth and survival. The growth inhibitory effect of AUY922 was further confirmed in a mouse xenograft model. These findings indicate the potential use of AUY922 in B cell lymphomas.